TANTANGAN GURU BAHASA INDONESIA TERHADAP PEMBELAJARAN BAHASA DI SEKOLAH - Ari Sugiarti (Khazanah Pendidikan, 2014)
Basically, the duty of Indonesia teacher is not only to deliver a group of materials need to be mastered. But, it is also their duty to make the students accustomed to use Indonesian correctly. This article discusses about the trouble faced by Indonesia teacher in teaching activity. At least, there are 5 trouble faced by teacher in lesson teaching, they are (1) Indonesian teaching materials which are too complicated, (2) dynamic language development, (3) the influence of native language, (4) lack of attention from other subjects, and (5) imbalanced between teaching process and real life. These troubles can be solved through some steps, such as the simplification of Indonesian teaching materials, the function firmness between the usage of standard and non-standard language,hold continuous language construction, support from oher subjects, and support from other various social stratum. Key words: teacher challenges, issues of language, standard language